Perancangan Sistem Informasi Reservasi Booking dan Reminder Service Motor Pada Shoowroom Benelli - Mashud, Mashud; P, Ramlah (Aliansi Dosen Perguruan Tinggi Swasta Indonesia (Adpertisi), 2022)
The workshop is one of the business facilities that provides after-sales repair services to consumers. Punctuality is very important for repair service users. The reservation process for booking and reminder services carried out at the Benelli Showroom is still using the telephone system or coming directly to the workshop. This study aims to design an information system for booking reservations and service reminders that are effective, efficient, and easy to use by Service Advisors and Customers. In this study, qualitative data analysis methods were used. Qualitative data analysis is a research procedure that produces descriptive data in the form of written or spoken words from people and observable behavior. The method that can be used in system analysis is the PIECES method (performance, information, economy, control, efficiency, control, and service). . The design method of this system uses UML (Unifield Modeling Language), namely using use case diagrams, Class diagrams and Activity diagrams. The results of the design of the reservation information system for booking and motorbike service reminders can provide convenience and customer satisfaction in booking service, and simplify the work of service advisors.